STUDY ON PERCEIVED ORGANIZATIONAL SUPPORT OF BUDGET HOTEL EMPLOYEES DURING COVID-19 PANDEMIC IN SABAH - Mohd Aden Usly; Datu Razali Datu Eranza; Jabil Mapjabil; Siti Hasnah Tanalol; Andy Lee Chen Hiun (International Journal of Accounting, Finance and Business, 2020)
With COVID-19 in year 2020 giving impacts to tourism industry in Malaysia, the authors have conducted an industrial analysis on small and medium companies in Sabah. This paper provides on insight on the perceived organizational support of employees at budget hotel in Kota Kinabalu, Sabah during the pandemic period of COVID-19. Organizational support is an important factor in maintaining employees’ morale and it is crucial to know the perception of employees of the organizational support that they perceived to have from the employers and managers at workplace. With the feedback and response, industrialists especially managers are encouraged to communicate more with employees. The results suggested that employees perceived organizational supports as a whole, with lower score on the job. Therefore, the study concluded that job design can be an interesting factor to look at in managing human capital at this difficult time.